2022
DOI: 10.1371/journal.pgph.0000212
|View full text |Cite
|
Sign up to set email alerts
|

No impact of performance-based financing on the availability of essential medicines in Burkina Faso: A mixed-methods study

Abstract: Access to safe, effective, and affordable essential medicines (EM) is critical to quality health services and as such has played a key role in innovative health system strengthening approaches such as Performance-based Financing (PBF). Available literature indicates that PBF can improve EM availability, but has not done so consistently in the past. Qualitative explorations of the reasons are yet scarce. We contribute to expanding the literature by estimating the impact of PBF on EM availability and stockout in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…31 The situation of availability of essential CVD medicine in Burkina Faso might be due to contextual constraints and powerful concurrent policies, which make it difficult for a holistic change in essential medicine availability. 39 The availability of guidelines was among the lowest tracer in this study. Peck et al 5 reported in 2014 that in many facilities in Tanzania, guidelines, diagnostic equipment and first-line drug therapy for the primary care of NCD were inadequate, and the management, training and reporting systems were weak.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…31 The situation of availability of essential CVD medicine in Burkina Faso might be due to contextual constraints and powerful concurrent policies, which make it difficult for a holistic change in essential medicine availability. 39 The availability of guidelines was among the lowest tracer in this study. Peck et al 5 reported in 2014 that in many facilities in Tanzania, guidelines, diagnostic equipment and first-line drug therapy for the primary care of NCD were inadequate, and the management, training and reporting systems were weak.…”
Section: Discussionmentioning
confidence: 74%
“…To reduce the premature deaths from NCDs by 25% by 2025, as highlighted in the Global NCD plan, at least 50% of the eligible people must receive drug therapy and counselling (including glycaemic control) to prevent heart attacks and strokes 31. The situation of availability of essential CVD medicine in Burkina Faso might be due to contextual constraints and powerful concurrent policies, which make it difficult for a holistic change in essential medicine availability 39. The availability of guidelines was among the lowest tracer in this study.…”
Section: Discussionmentioning
confidence: 76%
“…A observação de abundância de medicamentos contraceptivos estocados, mas fora do alcance das mulheres, contrasta com a preconcepção comum de que os problemas de acessibilidade aos medicamentos em países de baixa renda se definem pela indisponibilidade de recursos públicos para aquisição, ou da insuficiência de produtos oriundos de ações humanitárias internacionais [28][29][30][31][32] . O caso observado revela que, se por um acaso o coordenador da unidade sanitária também entender que contracepção 'é coisa do Ocidente' e que tem que deixar as crianças nascerem, não haverá contraceptivos disponíveis nas unidades de saúde e, portanto, não haverá acesso a eles.…”
Section: Resultsunclassified
“…These items are particularly important in the treatment of obstetric complications, especially in the case of a CS. A recent study showed that in Burkina Faso, a PBF programme had no impact on the availability of essential medicine due to contextual constraints and other policies implemented in the country [ 27 ]. In Burkina Faso, the lack of material resources to perform CS is particularly problematic.…”
Section: Discussionmentioning
confidence: 99%